La sexualidad infantil y su influencia en el desarrollo psicosocial del niño dirigido a los padres de familia del primer año de educación básica de la escuela Manuel Salcedo en la provincia de Cotopaxi, cantón Latacunga, parroquia Eloy Alfaro en el año lectivo 2014-2015 - Obando López, Génesis Lizbeth (2015)
This literature review is conducted with the aim of describing childhood sexuality in the psychosocial development of children which is characterized by four important dimensions such as: biological, psychological, social and moral aspects; by taking into account these dimensions, we know that childhood sexuality is inherent in human beings. The purpose of the issue was to help parents understand that infantile sexuality has great importance in children in order to have a free and spontaneous development into the society, taking into account that the family, school and the type of culture play a fundamental role in the children psychosocial development until adolescence, also it helps parents destroy the stereotypes imposed by the culture and the changes that have been producing decade after decade and allowing to accept and respect their children as they choose to be, avoiding damage or psychological disorder when not accepted. The work has a qualitative approach, descriptive type, it was supported by the documentary research by building the theoretical foundation and field research through the observation, application of instruments and validation for analysis of results which permitted to state a proposal as a solution to the problem.